Predicting new potential antimalarial compounds by using Zagreb topological indices (2022)
Molecular topology allows describing molecular structures following a two-dimensional approach by taking into account how the atoms are arranged internally through a connection matrix between the atoms that are part of a structure. Various molecular indices (unique for each molecule) can be determined, such as Zagreb, Balaban, and topological indices. These indices have been correlated with physical chemistry properties such as molecular weight, boiling point, and electron density. Furthermore, their relationship with a specific biological activity has been found in other reports. Therefore, its knowledge and interpretation could be critical in the rational design of new compounds, saving time and money in their development process. In this research, the molecular graph of antimalarials already in the pharmaceutical market, such as chloroquine, primaquine, quinine, and artemisinin, was calculated and used to compute the Zagreb indices; a relationship between these indices and the antimalarial activities was found. According to the results reported in this work, the smaller the Zagreb indices, the higher the antimalarial activity. This relationship works very well for other compounds series. Therefore, it seems to be a fundamental structural requirement for this activity. Three triazole-modified structures are proposed as possible potential antimalarials based on this hypothesis. Finally, this work shows that the Zag